2017
DOI: 10.1002/ajim.22738
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of transitions from single to multiple job holding: Results of a longitudinal study among employees aged 45‐64 in the Netherlands

Abstract: ObjectivesTo construct prediction models for transitions to combination multiple job holding (MJH) (multiple jobs as an employee) and hybrid MJH (being an employee and self‐employed), among employees aged 45‐64.MethodsA total of 5187 employees in the Netherlands completed online questionnaires annually between 2010 and 2013. We applied logistic regression analyses with a backward elimination strategy to construct prediction models.ResultsTransitions to combination MJH and hybrid MJH were best predicted by a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 36 publications
(8 reference statements)
0
5
0
Order By: Relevance
“…Determinants of MJH may differ between workers in different age groups, and with different educational levels, and with different types of MJH, i.e. only jobs as an employee versus jobs as an employee as well as being self-employed [ 5 , 20 , 21 ]. Differences in determinants of MJH may be related to differences in reasons for MJH and experiences with MJH.…”
Section: Methodsmentioning
confidence: 99%
“…Determinants of MJH may differ between workers in different age groups, and with different educational levels, and with different types of MJH, i.e. only jobs as an employee versus jobs as an employee as well as being self-employed [ 5 , 20 , 21 ]. Differences in determinants of MJH may be related to differences in reasons for MJH and experiences with MJH.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has shown that employees without a permanent contract are more likely to have multiple jobs (5,6). This, however, does not mean that multiple-job holding is equivalent to precarious employment.…”
Section: Letter To the Editormentioning
confidence: 96%
“…One explanation could be that health status is a predictor of MJH, rather than an outcome (Jamal et al 1998). Previous research using the same cohort, however, found that health status did not contribute to predicting transitions from single job holding to multiple job holding (Bouwhuis et al 2017b). However, that study did not distinguish between subgroups of multiple job holders.…”
Section: Discussionmentioning
confidence: 92%